Genome sequence of the bioplastic-producing “Knallgas” bacterium Ralstonia eutropha H16 - Pohlmann, Anne; Fricke, Wolfgang Florian; Reinecke, Frank; Kusian, Bernhard; Liesegang, Heiko; Cramm, Rainer; Eitinger, Thomas; Ewering, Christian; Pötter, Markus; Schwartz, Edward; Strittmatter, Axel; Voß, Ingo; et al. (Nature biotechnology, 2006)
The H 2 -oxidizing lithoautotrophic bacterium Ralstonia eutropha H16 is a metabolically versatile organism capable of subsisting, in the absence of organic growth substrates, on H 2 and CO 2 as its sole sources of energy and carbon. R. eutropha H16 first attracted biotechnological interest nearly 50 years ago with the realization that the organism's ability to produce and store large amounts of poly[ R -(–)-3-hydroxybutyrate] and other polyesters could be harnessed to make biodegradable plastics. Here we report the complete genome sequence of the two chromosomes of R. eutropha H16. Together, chromosome 1 (4,052,032 base pairs (bp)) and chromosome 2 (2,912,490 bp) encode 6,116 putative genes. Analysis of the genome sequence offers the genetic basis for exploiting the biotechnological potential of this organism and provides insights into its remarkable metabolic versatility.